Understanding fathers’ roles: an evidence-based practice guide for family therapists - Bean, Mathew (Kansas State University, 2007)
Although the processes by which fathers’ presence in the home affect children’s development is not known exactly, ongoing research is making strides toward a greater understanding of this concept (Lamb, 2000). Much of the research conducted on fathering came from researchers’ applying measures and concepts developed to understand mothering. This comparison of fathering and mothering has yielded little understanding of the processes by which father involvement can influence child development and, only in recent decades, has fathering begun to be studied using separate measures designed specifically to understand the unique aspects of fathering (Marsiglio, Amato, Day, & Lamb, 2001). To date, the effects of father involvement in families have been highlighted as a key factor in child growth and development, prevention of poverty, and as a buffer against adolescent risk-taking behaviors (Day & Lamb, 2004). However, in some cases, father involvement can have a very negative effect on children in families, and counter examples of research, showing the deleterious effects of negative father involvement, add an important aspect to fathering studies (Pleck, 2003). Unfortunately, the contradictory opinions and information found in research literature offer practitioners limited information upon which to base their work with fathers and their families. The following is a review of current research literature on father involvement, with an emphasis on families with adolescents. Recent improvements in researchers’ understanding and measurement of father involvement offer practical information for mental health practitioners. The written portion of this report will review current research on father involvement with adolescent children, and then in the presentation, offer suggestions for applying current fathering research to counseling practice. The goal of this report is to offer information that will narrow the research to practice gap for those working with adolescents and their families. Despite the flurry of research on father involvement in recent decades, little appears to have been done to make this research readily available to practitioners. Thus, current practices are limited, in that they are not benefiting from past research on father involvement and are not evolving with improved conceptualization and measurement of fathering activities. Given the current emphasis on evidence-based practice, this report is meant to be an added resource for practitioners, intending to help fathers in families with adolescents. In addition to a critical review of key works focusing on the effects of father involvement on adolescent children, this report will add insight to the work that clinicians do by discussing current perspectives in the fathering literature and offering suggestions for applying these ideas in the talk-therapy arena. Father influence on children during adolescence is the focus of this report due to research evidence showing that fathers influence may become increasingly important in the later stages of child development. (Amato, 1994; Faber, Edwards, Bauer, & Wetchler, 2003).
Keywords: Father; Involvement; Therapy; Adolescent; Health Sciences, Human Development (0758); Psychology, Clinical (0622); Psychology, Social (0451); Social Work (0452)